2021
DOI: 10.1111/jfbc.13859
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective effect of hydromethanolic extract of Ayapana triplinervis leaves on indomethacin‐induced gastric ulcer in male Wistar rats

Abstract: This study investigated the gastroprotective effect of Ayapana triplinervis leaves against indomethacin‐induced gastric ulcer in male albino rat. Gastric ulceration was developed by single oral dose of indomethacin (30 mg/kg). Experimental rats were pretreated with omeprazole (positive control 20 mg/kg), hydromethanolic extract of A. triplinervis (200 mg/kg) for 28 days just before the indomethacin treatment. Free acidity, total acidity, pepsin activity and gastric volume, gastric pH, tumor necrosis factor‐alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Elevation of CD and MDA levels in gastric tissue in indomethacin treated rats indicates the involvement of oxidative injury 46,47 . Hydromethanol extract of leaves of AT have the potent antioxidant activity that scavenged the free radicals and protects the rats from indomethacin induced oxidative damage 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation of CD and MDA levels in gastric tissue in indomethacin treated rats indicates the involvement of oxidative injury 46,47 . Hydromethanol extract of leaves of AT have the potent antioxidant activity that scavenged the free radicals and protects the rats from indomethacin induced oxidative damage 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of Gastric pH: After sacrifice, gastric content was collected and centrifuged for 10 min at 1000 rpm (4°C) then the clear supernatant was collected and used for the determination of pH by using pH meter 20 .…”
Section: Group Xmentioning
confidence: 99%
“…It has been shown that HCl/EtOH stimulation results in activating NF-κB which leads to phosphorylation of IκBα and P50/P65 heterodimer, followed by translocation to the nucleus, thus prompting cells to secrete infammatory factors (e.g., TNF-α, IL-1β, and IL-6) and inducing an infammatory response [39]. Elevated levels of TNF-α could stimulate leukocytes to secrete more IL-1β and IL-6, thus causing even more potent infammatory response [40]. IL-1β is involved in ulcer formation [41], and elevated IL-1β exacerbates ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
“…The data were represented as mean ± SEM. The comparisons between the mean values of different groups were assessed by oneway analysis of variance (ANOVA), followed by multiple comparison two-tailed t test using SPSS software, version 16.0, which is installed in Microsoft Windows 10 operating system (Maity et al, 2021). A significant difference in means has been expressed at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%